Pengaruh Metode GASING ( GAmpang, aSyIk, dan menyenaNGkan) terhadap Kemampuan Berpikir Kreatif dan Kemampuan Pemecahan Masalah Pecahan Siswa SD - Andini Nur Lestari (Jurnal Inovasi Pendidikan Dasar, 2021)
This study aims to determine the effect of the GASING method on thinking creatively and solving mathematical problems in fraction material in 5th grade of SDN Kedoya Utara 01. This study uses an experimental method with a 2 x 4 factorial design. Data were analyzed through an independent sample t-test with the help of SPSS 24. The results show that the learning outcomes of students with high creative thinking skills were t-count of 4.634 > t-table 2.179 with a significance of 0.001 < 0.05. While the learning outcomes of students with high mathematical problem-solving abilities were t-count of 5.786 > t-table 2.200 with a significance of 0.00 < 0.05. Based on the results of data analysis, it can be concluded that the GASING Method research has a positive influence on the ability to think creatively and solve mathematical problems, especially on high-ability groups of students. The highest achievement lies in the smooth aspect of creative thinking and at the stage of carrying out plans in solving Mathematical problems. Keywords: GASING Method, Creative Thinking Ability, Mathematical Problem Solving Ability